ASOSIASI PENYAKIT ALERGI ATOPI DENGAN IgG ANTI HELICOBACTER PYLORI PENELITIAN OBSERVASIONAL KASUS KONTROL ANALITIK DI UNIT RAWAT JALAN PENYAKIT DALAM RSU Dr SOETOMO SURABAYA - PP, Agung; H, Novida; D, Fetarayani; A, Baskoro; G, Soegiarto; C, Effendi (journal of internal medicine, 2011)
Approximately 20% of the world populations suffer from IgE-mediated allergic diseases. Although genetic factors play an important role in the manifestation of allergic disease, the existence of other factors such as lifestyle factors, socioeconomic factors and presence of oro-fecal infection including Helicobacter pylori infection also take a part. This is based on the hygiene hypothesis that infections in childhood can reduce allergic diseases. We conduct a study to analyze negative association between allergic diseases with IgG anti Helicobacter pylori. This is a matched case control study involved 52 patients in Internal Medicine outpatient ward Dr. Soetomo Hospital Surabaya consisting of 26 patients with allergic diseases as a group of cases and 26 non-allergic patients as controls. Allergic disease was diagnosed by anamnesis, physical examination, and skin prick tests, whereas IgG anti Helicobacter pylori was measured using immune-chromatography technique. We found in the allergic group there were 19 patient (73.08%) with positive Helicobacter pylori and 7 patient (26.92%) with negative result.Whereas in control group there were 21 patient (80.77%) with positive Helicobacter pylori result and 5 patient (19.23%) were negative. Helicobacter pylori serology had protective effect to allergic disease (OR 0.67, CI 95%). Was the conclusion, there is negative association between atopic allergic diseases with IgG anti Helicobacter pylori